2021
DOI: 10.1002/cac2.12236
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pancreatic cancer by indocyanine green‐assisted fluorescence imaging in the first and second near‐infrared windows

Abstract: Dear Editor,In the United States, pancreatic cancer is considered the fourth most common reason for cancer-related deaths; over 53% of patients are diagnosed at end-stage with a 5year survival rate of less than 3% [1]. Incomplete removal of all cancerous cells generally leads to local recurrence of pancreatic cancer [2]. Thus, the detection of tumor margin status plays an essential role in the complete resection of pancreatic cancer. Most of the existing imaging modalities, like computed tomography and magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To investigate the biodistribution of ICPs@PDA:CuO 2 NPs in vivo , they were labeled with the widely used fluorescence dye indocyanine green (ICG). Tumor-bearing mice were intravenously injected with either free ICG or ICG-labeled ICPs@PDA:CuO 2 NPs and the images were acquired and are shown in Figure A (excitation ∼740 nm, emission ∼790 nm). The results showed that free ICG was rapidly distributed throughout the body within the first hour, with fluorescence intensity decreasing quickly at the tumor sites due to the small size of the ICG molecules.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the biodistribution of ICPs@PDA:CuO 2 NPs in vivo , they were labeled with the widely used fluorescence dye indocyanine green (ICG). Tumor-bearing mice were intravenously injected with either free ICG or ICG-labeled ICPs@PDA:CuO 2 NPs and the images were acquired and are shown in Figure A (excitation ∼740 nm, emission ∼790 nm). The results showed that free ICG was rapidly distributed throughout the body within the first hour, with fluorescence intensity decreasing quickly at the tumor sites due to the small size of the ICG molecules.…”
Section: Resultsmentioning
confidence: 99%
“…First, TRPC3 seems to be able to interact with indocyanine green (ICG), a clinically established dye for intraoperative fluorescence discrimination of target tissue during hepatocellular surgery. Recent clinical reports promote the use of ICG to detect pancreatic cancer lesions [ 32 , 33 ]. Our prediction data suggests a novel possible contributing factor for a mechanistic explanation to establish fluorescence-guided pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenously administered ICG binds to blood proteins such as albumin and tends to accumulate in certain types of cancer due to the overexpression of ICG-related transporters (Figure ). Due to this characteristic behavior, ICG has been used for the visualization of malignancies such as liver, pancreatic, stomach and colon cancers. It is also used for the identification of sentinel lymph nodes during breast cancer surgery. , …”
Section: Introductionmentioning
confidence: 99%